An Autopsy Case of β-Thalassemia Major Illuminating the Pathological Spectrum of the Disease. (4th May 2021) - Sood, Ridhi; Rastogi, Pulkit; Bansal, Deepak; Das, Reena; Sharma, Prashant; Gude, Geethanjali; Dhankar, Mukesh
Abstract: Despite declining rates worldwide, autopsy studies remain invaluable tools to expand existing knowledge on the pathophysiology of diseases, especially those with multisystem involvement. β-thalassemia major (β-TM) is a relatively common hemoglobinopathy in India and is characterized by a regular requirement for life-sustaining transfusions and chelation. The iron overload is an invariable side effect. This secondary hemosiderosis leads to several complications, primarily in the heart, liver, pancreas, and endocrine organs. Despite adequate transfusion and chelation, untransplanted patients may show early mortality for several reasons. We report a 10-year-old boy with β-TM who died with clinical possibilities of iron overload-related cardiac failure and pulmonary arterial hypertension. His autopsy revealed certain unique disease pathologies in the form of minimal cardiac fibrosis in the presence of significant cardiac siderosis and widespread endocrine damage due to iron-overload. A null-cell pituitary microadenoma, previously undescribed in thalassemia syndromes, was found. This report highlights the importance of the diminishing art of autopsy, without which these histopathological insights would not have emerged.